MENINGKATKAN KREATIVITAS GURU DALAM PEMBELAJARAN DARING MELALUI SUPERISI KLINIS KOLABORATIF DI SD NEGERI WIJIMULYO KAPANEWON NANGGULAN SEMESTER I TAHUN PELAJARAN 2021/2022 - Agnes Kristini; Rahmat Mulyono (STKIP Subang, 2022)
This research aims to increase teacher creativity in online learning through Supervisi Klinis Kolaboratif at SD Negeri Wijimulyo Kapanewon Nanggulan Semester I of the 2021/2022 Academic Year. This research is a school action research. The subjects in this study were 9 teachers at SD N Wijimulyo for the 2021/2022 academic year, consisting of six class teachers and three subject teachers. The instrument used is the observation instrument for teacher creativity in online learning. The data analysis technique used in this study is descriptive qualitative and quantitative in the form of percentages. The teacher's average score in the initial conditions was 67.6 with a completeness percentage of 22.22%. This condition experienced an increase in the average value in cycle I, which was 74.2 and the percentage of completeness was 44.44%, this increase still did not reach the target previously set. In siklus II, the average value of teacher creativity in online learning again increased by 80.3 with a creativity percentage of 77.8%. This shows that the targets previously set have been achieved, so the research was stopped in siklus II.